Comparison of Frequency and Circumstances of Falls Among Male and Female Transfemoral Prosthesis Users - Rehman, Zia; Jehanzeb , Amna (Journal of Prosthetics Orthotics and Science Technology, 2022)
Incidence of amputation rises sharply with age. Most of the amputation occur above the age of 65. Lower limb amputation has a significant impact on the functional ability of the patients. The phenomenon of falls is globally recognized as the most common problem identified by health care workers. The study design is a cross sectional survey to compare the frequency and circumstances of falls among male and female transfemoral prosthetic patients. Out of the 90 patients frequency of fall in ages group 1 (15-30) is n=20, age group 2 (31-45) is n=25, age group 3 (45-60) is n=31 and ages group 4 (60+) is n=14. Also the fall frequency is higher in male patients than female. N=14 reported falls on slippery surface while n=31 reported falls on non-slippery surfaces. Out of 90 patients with Trans femoral prosthesis user n=30 falls because of mobility system failure, n=39 falls because of impaired balance and n=1 falls because of sensory impairment. The results of this study suggest that fall is quite prevalent among ambulatory transfemoral prosthetic patients and should be prioritized to evaluate the circumstances surrounding the fall so that to reduce the future risk of fall.